Škodljiva navodila obvladujoče družbe v dejanskem koncernu - koncernski privilegij - Podgorelec, Peter (Pravni letopis, 2010)
In a de facto group the dominant company may exert detrimental influence on a dependent company only if it compensates the disadvantage incurred by the dependent company. Thus, in a de facto group only such detrimental influences are allowed which can be compensated later. If the dominant company exceeds the limits of detrimental influence we are dealing with total dependence, which is unlawful. This unlawful state can be removed if the dominant and dependent companies conclude a control contract. For all-embracing and intensive management of a group of companies the reformation from the de facto group into a contract-based group is usually necessary.
Keywords: gospodarske družbe; gospodarske pogodbe; koncerni; odškodnina; povezovanje; Skoda; škoda